PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP TINGKAT KREATIVITAS DAN HASIL BELAJAR PERKALIAN DAN PEMBAGIAN PECAHAN DI KELAS V SD - Chichi mogi (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
This study examines the effectiveness of the Problem Based Learning model in improving students’ creativity and learning outcomes in fraction multiplication and division at the elementary school level. The background of this research is the low level of students’ creativity and mathematics learning outcomes caused by teacher-centered learning and limited contextual problem-solving activities. The objective of this study is to analyze the effect of Problem Based Learning on students’ creativity and learning outcomes in mathematics. This research employed a quantitative approach using a quasi-experimental design. The participants consisted of fifth-grade elementary school students divided into an experimental class taught using the Problem Based Learning model and a control class taught using conventional instruction. Data were collected using a creativity questionnaire and mathematics achievement tests. The data were analyzed using t-tests and F-tests to determine differences and interaction effects. The results indicate that students taught using the Problem Based Learning model demonstrated significantly higher creativity and learning outcomes compared to students in the control class. In addition, there was a significant interaction between students’ creativity and learning outcomes in the implementation of Problem Based Learning. These findings highlight the importance of student-centered and problem-oriented learning approaches in enhancing creativity and academic achievement in elementary mathematics learning.